Australian Cleotychini planthoppers: review of the genus Cleotyche Emeljanov, 1997 with three new species (Hemiptera: Fulgoromorpha: Dictyopharidae) - Constant, Jérôme; Semeraro, Linda; Moir, Melinda L. (European Journal of Taxonomy, 2022)
The genus Cleotyche in the monotypic Australian planthopper tribe Cleotychini (Fulgoroidea: Dictyopharidae) is reviewed. The subgenus Griseotyche subgen. nov. is described to accommodate one species Cleotyche blanda Emeljanov, 2011 while the second species, C. mariae Emeljanov, 1997, is retained in the subgenus Cleotyche (Cleotyche) Emeljanov, 1997. Three new species of Cleotyche (Cleotyche) from Queensland, C. (Cleotyche) christinae sp. nov. from Cania Gorge National Park, C. (Cleotyche) francescoi sp. nov. from Eurimbula National Park and C. (Cleotyche) montana sp. nov. from Blackdown Tableland National Park are described and compared to the type species of the subgenus, C. (Cleotyche) mariae Emeljanov, 1997. Illustration of the type specimens, male and female whenever available, and a distribution map are provided for the five species of the genus. The male genitalia and habitat of the three new species are illustrated. The tribe Cleotychini now contains one genus, Cleotyche with two subgenera and five species. Biological, ecological and biogeographical information is provided where available for each species. The diversity of Australian Dictyopharidae and mimicry of jumping spiders (Araneae: Salticidae) in Cleotychini are discussed briefly.